THE SWOT ANALYSIS OF HALAL TOURISM OF AL QUR’AN AKBAR PALEMBANG - Mario Ardiansyah; Disfa Lidian Handayani; Fatimatuz Zuhro (CV. Era Digital Nusantara, 2022)
This thesis research departs from the existence of the Koran which has attracted the attention of the world community and has become one of the main tourist attractions of Palembang city from South Sumatra. Moreover, because the Koran was confirmed as the only largest Koran in the world and included in the list of the Indonesian Registration Museum (MURI). This study wants to examine the strategy of developing halal tourism in the Al-Quran Akbar Palembang by using SWOT analysis. Data collection through interviews and documentation. The data analysis technique is descriptive qualitative by describing and describing as clearly as possible all the problems in the problem formulation, systematically, factually and accurately. The conclusion of this research is the Strategy for Development of Al-Qur'an Akbar Halal Tourism, namely by means of promotion through social media so that the Al-Qur'an Akbar is better known by tourists both local and foreign, Installing CCTV cameras, adding security personnel, implementing health protocols and coordinating with local officials, such as the police. As well as cooperating with the Government to repair damaged roads and construct toll roads so that tourists can easily visit the Al Qur'an Al Akbar.